Indigenously controlled tourism as struggle for autonomy: the Pataxó Jaqueira Reserve in Brazil - Juliana Porsani; Rickard Lalander; Kari Lehtilä; Jocimar Da Conceição-Carvalho; Juari Braz-Bomfim (Revista Iberoamericana de Estudios de Desarrollo)
This study analyses the emblematic experience of an indigenous group in Brazil, the Pataxó, who was able to set up and exercise strong control over an indigenous tourism project: the Jaqueira Reserve. Based on document analysis, interviews, and observations, we show how the Jaqueira Reserve was consolidated not only as a strongly autonomous initiative but also as constituent of a greater quest for autonomy (to craft aspired livelihoods conducive to cultural revitalization and environmental protection). The Pataxó experience shows that indigenous tourism can be an instrument in greater indigenous struggles, and as such can develop not only despite marginalization but also against it.